CLAUZA OFERTEI CONCURENTE ÎN CONŢINUTUL CONTRACTULUI DE COMERŢ INTERNAŢIONAL - USM ADMIN (Studia Universitatis Moldaviae: Stiinte Sociale, 2011)
The competitor offer clause presents an efficient legal tool for counteraction of risks which appear in the international market, most frequently price risks and some non-currency risks. Nevertheless, respective clause comes closer to that of keeping the contract value and, especially, to the price revision clause, given the fact that the competitor clause represents a clause of contract adjustment to the new circumstances. The competitor offer clause is quite frequent stipulated in some long-run contracts; still no things embarrass the parties to include it in other categories of contracts. Under the competitor offer clause, the promissor has to choose between the acceptance of this offer and the contract cancellation. At the same time the beneficiary is on the inside track. On the one hand, the beneficiary benefits from the conjectural changes which have the direct relation to the contract in execution and on the other hand, in case when the promissor will not comply with the new conditions of the competitor offer imposed by the new conjuncture of the world market, the beneficiary will cancel the contract in execution in an absolutely legal way and will conclude a new contract with a tertiary offer under the conditions of a more advantageous offer. The competitor offer clause generates legal effects in favour of one party of the contract, usually in favour of buyer, but it can be stipulated in favour of the seller, too. The mentioned offer is invoked by the competing tertiary and comprises more advantageous conditions in order to produce legal effects, thus the offer should be sufficiently defined to express the offer’s intention to commit him legally in case of the offer’s acceptance, to be performed in a written form and materialized by means of a trade letter, to be strong, precise and complete, unambiguous and to be addressed to more determined persons, to emerge from a popular and serious tertiary supplier who possesses a strong position on the international market and is able to fulfil his obligations in case of acceptance. The efficient functioning of the competitor offer clause imposes some specific procedural implications between the contractual partners. They refer to certain notifications, which must reach a certain form, under certain conditions and terms in which they should be performed. Thus, the beneficiary is obliged to announce the promissor about a competitor offer existence and the latter is obliged to inform the buyer about the taken decision. As a rule, the notifications are made in a written form by means established by the parties in the contract.